I-BAR domain proteins: linking actin and plasma membrane dynamics - Zhao, Hongxia; Pykäläinen, Anette; Lappalainen, Pekka (Current opinion in cell biology, 2011)
Dynamic plasma membrane rearrangements occur during many cellular processes including endocytosis, morphogenesis, and migration. Actin polymerization together with proteins that directly deform membranes, such as the BAR superfamily proteins, is essential for generation of membrane invaginations during endocytosis. Importantly, recent studies revealed that direct membrane deformation contributes also to the formation of plasma membrane protrusions such as filopodia and lamellipodia. Inverse BAR (I-BAR) domain proteins bind phosphoinositide-rich membrane with high affinity and generate negative membrane curvature to induce plasma membrane protrusions. I-BAR domain proteins, such as IRSp53, MIM, ABBA, and IRTKS also harbor many protein–protein interaction modules that link them to actin dynamics. Thus, I-BAR domain proteins may connect direct membrane deformation to actin polymerization in cell morphogenesis and migration.